Controlling reproduction women, society, and state power - Riley, Nancy E. 1955-; Chatterjee, Nilanjana 1961- (Polity Press, 2023)
Controlling reproduction - who has children, how many, and when - is important to states, communities, families, and individuals across the globe. However, the stakes are even higher than might at first be appreciated: control over reproduction is an incredibly powerful tool. Contests over reproduction necessarily involve control over women and their bodies. Yet because reproduction is so intertwined with other social processes and institutions, controlling it also extends far into most corners of social, economic, and political life. Nancy Riley and Nilanjana Chatterjee explore how various social institutions beyond the individual - including state, religion, market, and family - are involved in the negotiation of reproductive power. They draw on examples from across the world, such as direct fertility policies in China and Romania, the influence of the Catholic Church in Poland and Brazil, racial discrimination and resistance in Mexico and the US, and how Japan and Norway use laws intended to encourage gender equality to indirectly shape reproduction. This engaging book sheds new light on the operations of power and gender in society. It will appeal to students taking courses on reproduction in departments of sociology, anthropology, and gender studies.